Reconstruction of Marine Fisheries Catches for the Republic of Malta (1950-2010) - KHALFALLAH, M.; DIMECH, M.; ULMAN, A.; ZELLER, D.; PAULY, D. (Mediterranean Marine Science, 2017)
The marine fisheries catches of Malta were reconstructed for the period 1950-2014, including for reported and previously unreported commercial large- and small-scale catches, unmonitored fisheries catches, i.e., subsistence and recreational fisheries, as well as major discards. The present study updates and improves a previous catch reconstruction for Malta for the 1950-2010 time period. Reconstructed marine fisheries catches for Malta are nearly 1.3 times the official landings reported by the FAO and national authorities on behalf of Malta, increasing from around 1,200 t·year-1 in the 1950s to 3,700 t·year-1 in the 2010s. The discrepancy between reported and reconstructed total catches is mostly due to the subsistence catches estimated, which here consist exclusively of on-board consumption and take-home catch of commercial fishers. While the Maltese fisheries statistical system includes procedures to estimate ‘unmonitored’ commercial landings, this contribution documents that it would be beneficial to also account for non-commercial catches.